Diagnóstico ecogeográfico e caracterização morfogenética de jabuticabeiras - Danner, Moeses Andrigo (2009)
The jabuticabeira (Plinia sp.) is native fruit specie of central-south of Brazil, belonging to the Myrtaceae family. Although it has great economic potential exploit, is still a typical fruit for gardens and rare are the references on dispersion, characterization of genetic diversity and reproductive system. These aspects are important to encourage future work on breeding program. Aiming to better know this species, observations and tests were performed on the geographical dispersion of native jabuticaba trees of the southwest of Paraná, Brazil, and characterization of genetic divergence between native plants, as well on the morphological characterization, reproduction mode, pollen viability and the chromosome number of cultivated genotypes of three species of jabuticabeira (P. cauliflora, P. jaboticaba and P. trunciflora). In the Southwest region of Paraná, native jabuticabeiras were located always in the highest part of the toposequence and tree height is related to the altitude of ocurrence. The soils where jabuticabeira grows up are clay, strongly acidic (pH almost 4.0), and with low saturation of bases. There are genetic variability between native jabuticabeira, especially between different places of occurrence. Among them CV5 and VT3 genotypes, showed high genetic diversity and superior agronomic traits. There is variability of characters of leaves, flowers and fruits between genotypes of the three species. The size of the fruit stalk can be used to differentiate them. Jabuticabeira needs a polinizer, especially Africanized bees (Apis mellifera) for flower fertilization and fruit set. The boric acid is needed in making a standard media for testing in vitro germination of jabuticabeira pollen. The pollen viability is greater six hours after anthesis, coinciding with the period of increased bee visitation. It is possible the conservation of jabuticabeira pollen for up to 90 days, if it has high initial germination (greater than 80%). The chromosome number of the three jabuticabeira species seems to be 2n = 22. However, these observations are not definitive and further studies are needed.